The impact of data mining tools on business problem solving processes in service industries in Malaysia - Paknejad, Seyed Mohammad (2013)
The purpose of the following study is to discover what are the factors and elements in the process of problem solving that will be affected by data mining technology that bring benefits and advantages to the service providers. The researcher according to the literature found three different elements that were suspicious to be affected elements. Time, cost, and efficiency are three determinants of the problem solving process that were tested by the study. The researcher aims to suggest a conceptual framework to illustrate the relations to make better understanding of the processes and explain the important role of data mining. By accepting the framework, competitive advantage is gained by data mining in the process of problem solving will be explainable.